Role of left atrial hypertension in pulmonary hypertension associated with bronchopulmonary dysplasia - Sullivan, Rachel T.; Tandel, Megha D.; Bhombal, Shazia; Adamson, Gregory T.; Boothroyd, Derek B.; Tracy, Michael; Moy, Amanda; Hopper, Rachel K. (Frontiers in Pediatrics, 2022)
Left atrial hypertension (LAH) may contribute to pulmonary hypertension (PH) in premature infants with bronchopulmonary dysplasia (BPD). Primary causes of LAH in infants with BPD include left ventricular diastolic dysfunction or hemodynamically significant left to right shunt. The incidence of LAH, which is definitively diagnosed by cardiac catheterization, and its contribution to PH is unknown in patients with BPD-PH. We report the prevalence of LAH in an institutional cohort with BPD-PH with careful examination of hemodynamic contributors and impact on patient outcomes. This single-center, retrospective cohort study examined children <2 years of age with BPD-PH who underwent cardiac catheterization at Lucile Packard Children’s Hospital Stanford. Patients with unrepaired simple shunt congenital heart disease (CHD) and pulmonary vein stenosis (only 1 or 2 vessel disease) were included. Patients with complex CHD were excluded. From April 2010 to December 2021, 34 patients with BPD-PH underwent cardiac catheterization. We define LAH as pulmonary capillary wedge pressure (PCWP) or left atrial pressure (LAP) of at least 10 mmHg. In this cohort, mean PCWP was 8 mmHg, with LAH present in 32% (n=11) of the total cohort. A majority (88%) of the cohort had severe BPD. Most patients had some form of underlying CHD and/or pulmonary vein stenosis: 70% (n=21) with an atrial septal defect or patent foramen ovale, 70% (n=21) with patent ductus arteriosus, 13% (n=12) with ventricular septal defect, and 13% (n=12) with pulmonary vein stenosis. Using an unadjusted logistic regression model, baseline requirement for positive pressure ventilation at time of cardiac catheterization was associated with increased risk for LAH (odds ratio 8.44, 95% CI 1.46-48.85, p= 0.02). Small for gestational age birthweight, sildenafil use, and CHD were not associated with increased risk for LAH. LAH was associated with increased risk for the composite outcome of tracheostomy and/or death, with a hazard ratio of 6.32 (95% CI 1.72, 22.96; p=0.005). While the etiology of BPD-PH is multifactorial, LAH is associated with PH in some cases and may play a role in clinical management and patient outcomes.